Cell-Free Biomimetic Osteochondral Scaffold: Implantation Technique. Issue 3 (July 2019) - Sessa, Andrea; Perdisa, Francesco; Di Martino, Alessandro; Zaffagnini, Stefano; Filardo, Giuseppe
Abstract : Background: This 1-stage cell-free scaffold-based technique is indicated for the treatment of full-thickness chondral and osteochondral lesions in the knee, regardless of the lesion size. The aim of the procedure is restoration of the osteochondral unit while avoiding the issues of donor site morbidity and those related to cell management. Description: The surgical technique is simple and can be performed as a 1-stage procedure. The lesion site is visualized through a standard knee medial or lateral parapatellar arthrotomy. The defect is prepared by excision of the injured cartilage and subchondral bone to ensure adequate bone-marrow blood flow and to create a squared, regularly shaped lodging for the device. The scaffold is then shaped and sized according to the dimensions of the prepared lesion site and implanted by press-fitting or with addition of fibrin glue. Finally, the complete range of motion is tested to assess the stability of the implant before and after releasing the tourniquet. Alternatives: Nonsurgical alternatives have been reported to include nonpharmacological modalities, such as dietary supplements, and pharmacological therapies as well as physical therapies and novel biological procedures involving injections of various substances1 . There are several surgical alternatives, including among others microfracture, mosaicplasty, osteochondral allograft, and total knee arthroplasty, depending primarily on the disease stage and etiology as well as the specific patient conditions2, 3 . Rationale: This cell-free device is engineered in 3 layers to mimic the structure and composition of the osteochondral unit in order to guide resident cells toward an ordered regeneration of both bone and cartilage layers, providing a better quality of regenerated articular surface. The treatment approach offers a useful alternative to current procedures in the field of osteochondral lesions, in particular for young and middle-aged patients affected by symptomatic defects in which subchondral bone is likely involved. The advantages of this scaffold include the ability to perform a 1-stage surgical procedure, off-the-shelf availability, a straightforward surgical technique, and lower costs compared with cell-based regenerative options. Furthermore, in contrast to some more traditional treatments, it can be used for large lesions.